SCIENTISTS WITH BUSINESS KNOWLEDGE WILL FLY HIGH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 November 2016 – Scientists as well as science students will fly high if they are equipped with business knowledge and have a strong network with those in the corporate world.